Between Deleuze and Foucault - Morar, Nicolae, 1979-; Nail, Thomas; Smith, Daniel W. (Daniel Warren), 1958-; Deleuze, Gilles, 1925-1995; Foucault, Michel, 1926-1984 (Edinburgh University Press, 2016)
Deleuze and Foucault had a long, complicated and productive relationship, in which each was at various times a significant influence on the other. This collection combines 3 original essays by Deleuze and Foucault, in which they respond to each otheŕ⁰₉s work, with 16 critical essays by key contemporary scholars working in the field. The result is a sustained discussion and analysis of the various dimensions of this fascinating relationship, which clarifies the implications of their philosophical encounter.